The Effect of Market Orientation And Entrepreneurship Orientation on Marketing Performance Mediated By Marketing Capability (A Study of the Furniture Industry in Probolinggo Regency) - Salman AL Farizy; Nur Hidayati; Siti Asiyah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to examine the effect of market orientation and entrepreneurial orientation on marketing performance through marketing capability (a case study in the industry in Probolinggo Regency). This study uses a quantitative approach with primary data from 73 respondents collected using purposive sampling. The analysis tool used is SEM-PLS with SmartPLS software. The results show that market orientation and entrepreneurial orientation have a significant positive effect on marketing capability, but market orientation and entrepreneurship have no direct effect on marketing performance. Marketing capability has a significant positive effect on marketing performance. Furthermore, market orientation and entrepreneurial orientation through marketing capability have a significant positive effect on marketing performance. The results of this study indicate the importance of improving market orientation and entrepreneurial orientation to build marketing capability, while marketing capability can enhance marketing performance. Further research is expected to use broader variables such as product innovation, product quality, and price.